The democratization of higher learning in Malaysia: Its euphemism - Bahrom, Hasan; Abu Amrin, Ahmad Nawir; Wahab, Samsudin (2004)
This concept paper discusses the euphemism of our learning-for-all policy that has been the hallmark of our education aspirations. Has it really been there for those who aspire to answer the calling? Has it really rubbed down on us, every single citizen of Malaysia, that the system and values that wehaven our education mainstream accommodate our needs and wants of being an integral part of educated Malaysia? Does it really matter to be academically educated when it only calls for a sound healthy mind, physique and not forgetting network to earn and support a living in this beautiful and beloved country of ours? These are very thoughtful indeed what with our status as a developing country where survival based on Ringgit Malaysia and sen is still the order of the day for our countrymen.